Imaging of Reparable and Irreparable Rotator Cuff Tears - Murthy, Sindhoora; Shen, Michelle; Lemos, Diego F.; Alaia, Michael J.; Alaia, Erin F. (Seminars in Musculoskeletal Radiology, 2025)
This review offers a comprehensive discussion of magnetic resonance imaging (MRI) for the assessment of rotator cuff tendon repair and joint-preserving surgical options for patients with irreparable rotator cuff tears. Deciding to proceed with arthroscopic repair of a rotator cuff tendon tear is impacted both by clinical factors and morphological imaging features. Preoperative clinical and imaging features also predict the likelihood of success of a rotator cuff tendon repair and are important to recognize. In patients with irreparable rotator cuff tears and relatively preserved glenohumeral cartilage, various joint-preserving surgical options are available and seen increasingly in clinical practice.The acceptable range of postoperative imaging findings correlating with a functionally intact rotator cuff repaired tendon, and MRI findings that are either suggestive of or definitive for rotator cuff tendon repair failure are discussed in detail, with attention to the Sugaya classification. Ancillary features, such as progressive retraction of the myotendinous junction and the degree of muscle fatty atrophy, can be used as problem-solving tools in cases equivocal for rotator cuff retear. Finally, this review discusses in detail the most common joint-preserving treatment options for patients with irreparable rotator cuff tears, including an in-depth focus on superior capsular reconstruction.
Keywords: rotator cuff; repair; outcomes; irreparable; reparable